Implementasi K-Means Clustering dalam Mengklasifikasi Pengaruh Les Terhadap Prestasi Siswa dengan Metode Elbow - Habibie, Alief Fathul; R, Rakhmat Kurniawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Student achievement and ability are very important perspectives to consider. In this regard, Madrasah Ibtidaiyah Swasta (MIS) Al-Falah Medan is an educational institution that has a good reputation in both religious and other sciences. This study aims to analyze the influence of tutoring on student achievement at Madrasah Ibtidaiyah Swasta (MIS) Al-Falah Medan using the K-Means Clustering method and the Elbow technique to determine the optimal number of clusters. The data used in this research involves 514 students from classes 1A to 6B, with the analyzed variables including semester exam scores, participation in additional tutoring, and extracurricular activities. The analysis results show that students who participate in additional tutoring have higher average scores compared to those who do not. The average score of students in the semester exams is 87.71, while the average score for students participating in tutoring and extracurricular activities is 87.12. The clustering process results in four groups of students, with the highest performing group in cluster 2, while the lowest performing groups are in clusters 3 and 4. This research provides important information for the school in understanding the impact of tutoring on students' academic performance and can be used to improve learning strategies at MIS Al-Falah Medan.